2000
DOI: 10.1177/0148607100024004210
|View full text |Cite
|
Sign up to set email alerts
|

Semiquantitative Culture of Subcutaneous Segment for Conservative Diagnosis of Intravascular Catheter‐Related Infection

Abstract: These results indicate that the combined subcutaneous segment and hub culture constitutes an easy, effective procedure for the conservative diagnosis of catheter colonization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…[20] According to Fortun et al ., the rate of incidence of tip colonization was 2.9 per 1000 catheter-days and of bacteremia was 1.2 per 1000 catheter-days. [21] Similarly, Deshpande et al . in 2005 in their study reported that the incidence of catheter infection was 4.01/1000 catheter-days (2.29% catheter) and colonization was 5.07/1000 catheter-days (2.89% catheters), which was low.…”
Section: Discussionmentioning
confidence: 99%
“…[20] According to Fortun et al ., the rate of incidence of tip colonization was 2.9 per 1000 catheter-days and of bacteremia was 1.2 per 1000 catheter-days. [21] Similarly, Deshpande et al . in 2005 in their study reported that the incidence of catheter infection was 4.01/1000 catheter-days (2.29% catheter) and colonization was 5.07/1000 catheter-days (2.89% catheters), which was low.…”
Section: Discussionmentioning
confidence: 99%
“…These may prevent unnecessary catheter changes for diagnostic purposes. Sensitivity can be improved by swabbing and culturing not only the skin at the insertion site but also 1 cm of the subcutaneous portion of the catheter, once it has been pulled away to do so 69 . Besides, when superficial skin cultures are performed in patients with a high suspicion of CR-BSI, the positive predictive value rises to almost 100% 70 .…”
Section: Conservative-procedures To Assess Crimentioning
confidence: 99%
“…Cultures of the hub alone do not improve the situation, as hub sensitivity was found to be 61% [41]. However, when cultures of both the skin and the hub are taken in combination, sensitivity improved to 86%, though specificity and the positive predictive value remain low.…”
Section: Skin And/or Hub Culturesmentioning
confidence: 95%
“…The area chosen is swabbed then the swab is streaked onto agar and cultured semiquantitatively [40]. Fortun et al [41] found that skin culturing, as a diagnostic test for catheterrelated infection, yielded less than or equal to 61% sensitivity, 72% specificity, and 62% positive predictive value. However, in cases where infection is suspected and quantitative skin cultures of the CVCs are taken, sensitivity rises to 75%, specificity to greater than 90%, and the positive predictive value to 100% [42].…”
Section: Skin And/or Hub Culturesmentioning
confidence: 99%